The Effect of Specific Heat Ratio on Neutron Yield - Saw, S. H.; Chong, Perk Lin; Rawat, Rajdeep S.; Tan, Claudia Li Ching; Lee, Paul; Talebitaher, Alireza; Lee, Sing (IEEE, 2014)
It is known that the radius ratio of a plasma pinch depends on the specific heat ratio γ of the pinch plasma, where radius pinch ratio is defined as: radius of plasma pinch column/radius of anode. The lower the specific heat ratio the lower would be the pinch radius ratio with corresponding increased compression and pinch density. The deuterium plasma focus pinch is invariably fully ionized and has a specific heat ratio of practically the highest possible value of 5/3. If the deuterium plasma focus could have its specific heat ratio reduced below 5/3 we might expect its radius ratio to be correspondingly reduced, increasing the pinch density, thus improving the D–D fusion neutron yield. To demonstrate this effect we run the Lee model code in deuterium but hypothetically fix the specific heat ratio, reducing it at each run. The results show that indeed the radius ratio is reduced, increasing the compression, and the neutron yield is substantially increased. The effect is used to explain the observed neutron yield enhancement when a deuterium plasma focus doped with a small amount of krypton.